Using community-based participatory approaches to improve access to mass drug administration for trachoma elimination in a pastoral conflict area of Kenya. - Paul M Gichuki; Bridget W Kimani; Tabitha Kanyui; Collins Okoyo; Titus Watitu; Wyckliff P Omondi; Doris W Njomo (PLoS Neglected Tropical Diseases)
In Baringo County, Kenya, trachoma remains endemic despite repeated mass drug administration (MDA) efforts, with coverage in one of the wards consistently falling short of world health organization (WHO) targets. The disease is endemic in 12 out of the 47 counties in Kenya. Baringo county is a pastoral conflict, hard to reach area where eight rounds of mass drug administration (MDA) for trachoma have been implemented. In Loyamorok ward, treatment coverage has been below 68% against the WHO recommended threshold of 80%. Community engagements that promote participatory approaches are key to MDA success. In this study, we describe community-based participatory approaches qualitatively developed and implemented during the intervention phase of a study that involved a pre-intervention, intervention and post intervention phases and aimed to address barriers of community participation and access to trachoma MDA. Interviews and focus group discussions were used to identify barriers to community participation in MDA, that included power and gender dynamics, rampant insecurity, community myths and misconceptions, migration in search of water and pastures, vastness and terrain and ineffective teams which resulted to unsupervised swallowing of drugs during MDA campaigns. Stakeholders in trachoma were identified through meetings with national, county and sub-county health management teams. The stakeholders, community members and the research team used the identified barriers to formulate MDA strategies including effective stakeholder engagement, enhanced social mobilization, community awareness creation on trachoma, effective planning and execution of MDA and implementation monitoring of the MDA campaign, all aimed at increasing MDA coverage. Overall MDA coverage in the area increased from 67.6% in 2021 to 87% in 2023 thus meeting the WHO threshold of 80%. The use of community-based, participatory approaches in the development and implementation of data driven strategies has the potential to positively influence MDA coverage for trachoma, and other neglected tropical diseases.